Geospatial analysis of changes in vegetation cover over Nigeria - Fashae, Olutoyin; Olusola, Adeyemi Oludapo; Adedeji, Oluwatola (Bulletin of Geography. Physical Geography Series, 2017)
Vegetation cover over Nigeria has been on the decrease recently, hence the need for adequate monitoring using geo-information technology. This study examined the spatio-temporal variation of vegetation cover over Nigeria for thirty years with a view to developing a strategy for enhancing environmental sustainability. The study utilized satellite imageries between 1981 and 2010 using Normalised Difference Vegetation Index (NDVI) to predict the spatial extent of vegetation cover in 2030 coupled with cellular automata and markov chain techniques in ArcGIS 10.3. The results showed that dense vegetal areas decreased from 300,959.48 km2 in 1981 to 46,662.30 km2 in 2010, low vegetal areas increased from 35,305.33 km2 in 1981 to 364,533.77 km2 with a further increase of 422,429km2 from the 2030 prediction.